2004
DOI: 10.1136/adc.2003.044156
|View full text |Cite
|
Sign up to set email alerts
|

Nephrolithiasis associated with ceftriaxone therapy: a prospective study in 51 children

Abstract: Background: Background: Ceftriaxone, a third generation cephalosporin, is widely used for treating infection during childhood. The kidneys eliminate approximately 33-67% of this agent, and the remainder is eliminated via the biliary system. Ceftriaxone may bind with calcium ions and form insoluble precipitate leading to biliary pseudolithiasis. The aim of this study was to assess whether ceftriaxone associated nephrolithiasis develops by the same mechanism, and whether this condition is dose related. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 12 publications
(11 reference statements)
3
78
4
Order By: Relevance
“…Approximately 33% to 67% of ceftriaxone is excreted unmetabolized in the urine, whereas the remainder is excreted through biliary elimination. 1 Clinical studies have demonstrated that ceftriaxone can cause biliary pseudolithiasis, 2,3 nephrolithiasis, [4][5][6][7] and bladder sludge, 8 especially in children.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 33% to 67% of ceftriaxone is excreted unmetabolized in the urine, whereas the remainder is excreted through biliary elimination. 1 Clinical studies have demonstrated that ceftriaxone can cause biliary pseudolithiasis, 2,3 nephrolithiasis, [4][5][6][7] and bladder sludge, 8 especially in children.…”
Section: Resultsmentioning
confidence: 99%
“…4,6,7 After cessation of ceftriaxone therapy, the stones vanish by themselves. With this view, we initiated pharmacotherapy for all children upon diagnosis, and 9 children responded well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftizoxime undergoes biotransformation in liver to inactive form metabolite resulting in decrease concentration in blood (Sar et al 2006, Bakul et al 2009). The drug is primarily eliminated via the kidneys (33-67%) with remainder eliminated via the biliary system and bind with calcium ions producing biliary pseudolithiasis (Avci et al 2016). The liver eliminates a considerable proportion of ceftriaxone in the form of a soluble salt (Avci et al 2016), ceftriaxone is an anion when its concentration become high these anions bind with calcium ions to form insoluble complexes that precipitate out the biliary system (Shiffman et al 1990, Park et al 1991 Combination of herbs with chemotherapy may be used to decrease adverse effects, elevate the immune function and improve the quality of life in the patients (Ragaa et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The drug is primarily eliminated via the kidneys (33-67%) with remainder eliminated via the biliary system and bind with calcium ions producing biliary pseudolithiasis (Avci et al 2016). The liver eliminates a considerable proportion of ceftriaxone in the form of a soluble salt (Avci et al 2016), ceftriaxone is an anion when its concentration become high these anions bind with calcium ions to form insoluble complexes that precipitate out the biliary system (Shiffman et al 1990, Park et al 1991 Combination of herbs with chemotherapy may be used to decrease adverse effects, elevate the immune function and improve the quality of life in the patients (Ragaa et al 2011). Hypothesis of this study is Matricaria Chamomilla extract has protective effect on hepato-renal toxicity which induced during ceftriaxone injection in male albino rats by monitoring the biochemical changes in serum and histopathological findings in liver and kidney.…”
Section: Introductionmentioning
confidence: 99%